Aktuelle Empfehlungen der DGPPN für Schizophrenie-Qualitätsindikatoren = DGPPN recommendations on quality indicators for schizophrenia - Großimlinghaus, Isabell; Meyer-Lindenberg, Andreas (Der Nervenarzt, 2017)
Background: In Germany, several quality indicators have been proposed for the measurement of quality of mental healthcare. Some of these quality indicators have been tested in feasibility studies. The German Association for Psychiatry and Psychotherapy (DGPPN) established the “Task Force Quality Indicators (QI)” that, based on previous experience in the development and pilot testing of indicators, considered the further development and practical realization of QI for schizophrenia. Aim: The aim was to select a set of QI for schizophrenia that can also be applied to other diagnoses or used in generic measurements. Another goal was to focus on high feasibility of indicators. Methods: In a multistage selection process, the DGPPN Task Force selected QI that focus on essential quality aspects from an inventory of 161 existing QI developed by national and international research groups. Indicators were adapted in consultation with the “trialogic forum” of the DGPPN. Results: The DGPPN proposes the following ten indicators for quality measurement in mental healthcare for schizophrenia: QI1 Long-term treatment/Monitoring of side effects, QI2 Seclusion and restraint, QI3 Number of suicides, QI4 Psychoeducational-oriented intervention for significant others, QI5 Timely beginning of outpatient treatment after discharge from inpatient treatment, QI6 Aggression management - inpatient treatment, QI7 Diagnostic procedures/Physical examination, QI8 Antipsychotic polypharmacy, QI9 Rehabilitation/Vocational rehabilitation, QI10 Diagnostic procedures/Psychosocial functioning. Discussion: Most of our proposed QI have to be measured by means of additional data documentation. Based on prior experience in the pilot testing of QI, the DGPPN estimates that the additional efforts in data documentation would be manageable, but have to be refinanced. The indicators will be tested in feasibility studies in different mental healthcare hospitals in Germany.